2009
DOI: 10.1097/aln.0b013e3181a91957
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic-induced Preconditioning Delays Opening of Mitochondrial Permeability Transition Pore via  Protein Kinase C-ϵ–mediated Pathway

Abstract: Background Cardioprotection by volatile anesthetic-induced preconditioning (APC) involves activation of protein kinase C (PKC). The current study investigated the importance of APC-activated PKC in delaying mitochondrial permeability transition pore (mPTP) opening. Methods Rat ventricular myocytes were exposed to isoflurane in the presence or absence of nonselective PKC inhibitor chelerythrine or isoform-specific inhibitors of PKC-δ (rottlerin) and PKC-ε (myristoylated PKC-ε V1-2 peptide), and the mPTP openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 52 publications
8
88
0
Order By: Relevance
“…The cardiac activity of CST is achieved through signalling pathways expected for receptor-orphan peptides with membraneinteracting properties [4]. Here, using classic antagonists [14,35,39,[41][42][43][44], we demonstrated for the first time that the cardioprotective effect of CST-Post depends on the activation of PI3k/Akt, PKCs and of mitoK ATP channels, which may include a ROS signalling. The prevention of mPTP opening in myocytes challenged with oxidative stress reinforces the idea that CST protective effects converge on mitochondria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cardiac activity of CST is achieved through signalling pathways expected for receptor-orphan peptides with membraneinteracting properties [4]. Here, using classic antagonists [14,35,39,[41][42][43][44], we demonstrated for the first time that the cardioprotective effect of CST-Post depends on the activation of PI3k/Akt, PKCs and of mitoK ATP channels, which may include a ROS signalling. The prevention of mPTP opening in myocytes challenged with oxidative stress reinforces the idea that CST protective effects converge on mitochondria.…”
Section: Discussionmentioning
confidence: 98%
“…In Group 5 a specific PKCε inhibitor, εV1-2, was used to test the involvement of this kinase (εV1-2 1μM; CST-Post+εV1-2 Group) [44].…”
Section: Cardiac Function and Infarct-size Studiesmentioning
confidence: 99%
“…H 2O2 was not used to trigger mPTP opening, since it caused cell hypercontracture, which hampered identification of pore opening. Instead, mPTP opening was instigated using a well-established approach, where oxidative stress was induced by laser-photoexcitation as described below and previously (42). H 2O2 alone did not affect fluorescence probes [except 5-(and-6)-chloromethyl-2=,7=-dichlorofluorescein (CM-DCF)], as measured by spectrofluorometry.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac mitochondria were isolated from Wistar rats as reported previously (42). Hearts were placed in cold isolation buffer [in mM: 50 sucrose, 200 mannitol, 5 KH 2PO4, 1 EGTA, 5 3-(N-morpholino) propanesulfonic acid, and 0.1% bovine serum albumin; pH 7.3 adjusted with KOH] and homogenized with a T 25 disperser (IKA-Werke, Staufen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found that the volatile anesthetics such as isoflurane and sevoflurane induce cardioprotection by preconditioning and postconditioning (Bouwman et al, 2010;Inamura et al, 2010;Inamura et al, 2009;Kaneda et al, 2008;Okusa et al, 2009;Weber et al, 2005). Pravdic et al demonstrated that isoflurane preconditioning delays MPTP opening using the tetramethyl-rhodamine ethyl ester (TMRE) technique in rat cardiomyocytes (Pravdic et al, 2009). Also, it has been reported that atractyloside, a MPTP opener, abolished cardioprotection by isoflurane postconditioning (Krolikowski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%